A hybrid FD-DEM solver for rigid particles in viscous fluid. (2nd September 2015) - Wu, Shifeng; Yuan, Li
Highlights: An improved FD method for a solid–fluid system is developed. The method avoids the need to use Lagrange multipliers for the rigid body motion. The collision force acting on each colliding particle is computed by DEM. The new method can be generalized for collisions including friction. Several benchmark problems show the effectiveness of the present method. Abstract: In this article, the dynamics of colliding particles immersed in a viscous fluid is numerically investigated. An improved fictitious domain (FD) method for a solid–fluid system is developed and a collision strategy for multiple particles is presented. In earlier methods, a repulsive force is applied to the particles when their separation distance is less than a critical value and depending on the magnitude of this artificial repulsive force, collision of two or more particles may bounce unrealistically. In the present method, when the collision of two or more particles happens, the collision force acting on each colliding particle is determined by using the Discrete Element Method (DEM). Furthermore, the improved FD method employs a discrete δ -function in the form of bi-function to transfer quantities between the Eulerian and Lagrangian nodes similar to the immersed boundary method. This feature avoids the need to use Lagrange multipliers for imposition of the rigid body motion. Numerical results for motions of one or several particles in a viscous fluid are presented.